Occurrence of Cronobacter spp. in retail foods - Hochel, I; Růžičková, H; Krásný, L; Demnerová, K (Journal of applied microbiology, 2012)
AIMS: To study the occurrence of Cronobacter spp. in foods and to investigate the phenotypic properties of the strains isolated. METHODS AND RESULTS: A total of 53 strains of Cronobacter spp. isolated from 399 food samples were identified using conventional biochemical methods and MALDI-TOF mass spectrometry. Foods of plant origin were the most frequently contaminated samples. No Cronobacter spp. were found in infant milk formula, wheat-based infant food, pasteurized and raw cow milk, mincemeat, chicken, chickpea and potato dumpling powder. The individual species were identified as Cronobacter sakazakii (54·7%), Cronobacter malonaticus (28·4%), Cronobacter dublinensis (7·5%), Cronobacter muytjensii (7·5%) and Cronobacter turicensis (1·9%). Cronobacter sakazakii and C. malonaticus belong to biotype 1, 2, 2a, 3, 4 and 5, 5a, respectively. Cronobacter dublinensis strains were subdivided into biotypes 6 and 12. All strains were resistant to erythromycin and two of them were resistant to both erythromycin and tetracycline. CONCLUSIONS: Cronobacter spp. were isolated from various food samples pre-eminently of plant origin and dried food ingredients. SIGNIFICANCE AND IMPACT OF THE STUDY: These findings will increase and detail our knowledge of the presence and diversity of Cronobacter spp. in foods.
Keywords: Česká republika; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Czech Republic; enterobakteriální infekce; DNA, Bacterial; Enterobacteriaceae Infections; DNA bakterií; Food Microbiology; lidé; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Cronobacter; Humans; Cronobacter sakazakii; potravinářská mikrobiologie